Grasping and manipulation of a micro-particle using multiple optical traps. (June 2016) - Cheah, Chien Chern; Ta, Quang Minh; Haghighi, Reza
Abstract: In existing control techniques for optical tweezers, a target particle is directly trapped and manipulated by a single laser beam. However, a typical force generated by an optical trap is extremely small (on the order of piconewtons) and thus it is not sufficient to manipulate a large cell or object. Besides, the feasibility of optical manipulation also depends on the physical properties of the specimen. An opaque object or object with the same refractive index as the fluid media may not be trapped directly by the laser beam. Therefore, current control techniques for optical tweezers cannot be utilized to manipulate various types of cells or objects, including untrappable or large ones. In this paper, robotic control techniques are developed for optical tweezers to achieve grasping and manipulation of a microscopic particle, which is beyond the capability of a single optical trap. First, multiple laser beams are generated, and each laser beam is utilized to trap and drive one grasping particle to form a desired shape around the target particle. A grasping formation of trapped particles is thus generated to hold the target particle. Then the target particle is manipulated to a desired position by controlling the motorized stage. The proposed control strategy is particularly suitable for manipulation of large particles, or even untrappable cells or objects. Rigorous mathematical formulations have been developed to analyze the control system for grasping and manipulation of the microscopic particle. Experimental results are presented to illustrate the performance of the proposed grasping and manipulation techniques.